História, a gente aprende vivendo : o ensino da história egípcia entre a prática em sala de aula e a proposta curricular do novo ensino médio da Paraíba (2016-2021) - Silva, Wanderson Alberto da (2023)
This dissertation, linked to the line of research Teaching History and Historical Knowledge, aims to investigate the teaching of Ancient Egypt, in the History curricular component between the years 2016 and 2021. This focus is justified in view of the emergence of mandatory educational reform in Brazil for the implementation of the New Secondary Education, which should take place from January 2022, in accordance with Law 13.415/17. Seeking to find ways for discussions that expand debates on the teaching of History, we chose as a methodological procedure the analysis of teaching experiences, based on the elaboration of a Research Questionnaire, whose study material was the experiences of teachers from public and private schools. who teach History in the first year of high school in Paraíba. With the results of the questionnaire we realized that, regardless of the public or private sphere, there were not many changes. The experiences of teachers in the classroom demonstrate in their teaching practices that Ancient Egypt, undoubtedly appreciated by students, is not developed in its diverse possibilities of approaches available in the current State curriculum. Also according to the questionnaire, these same teachers did not undergo ongoing training on educational standard documents, such as the National Common Curricular Base (BNCC) and the Secondary Education Curricular Proposal (PCEM/PB).